Contralateral unaffected breast augmentation using zone IV as a SIEA flap during unilateral DIEP flap breast reconstruction. Issue 9 (September 2019) - Satake, Toshihiko; Muto, Mayu; Kou, Seiko; Yasumura, Kazunori; Ishikawa, Takashi; Maegawa, Jiro
Abstract: Background: Contralateral breast augmentation during unilateral breast reconstruction is a good option for women with small breasts. In patients with adequate lower abdominal tissues, the deep inferior epigastric perforator (DIEP) flap is often the first choice for unilateral autologous breast reconstruction. We use Zone IV, which is usually excised owing to its insufficient blood circulation, as a superficial inferior epigastric artery (SIEA) flap for contralateral breast augmentation. Methods: Between October 2004 and January 2016, 32 patients underwent unilateral breast reconstruction using a DIEP flap and an attempted simultaneous contralateral breast augmentation with an SIEA flap. The unilateral DIEP flap attached to the contralateral SIEA flap was split into two separate flaps after indocyanine green angiography. In all patients, ipsilateral internal mammary vessels were used as recipient vessels for DIEP flap breast reconstruction. The SIEA flap pedicle was anastomosed to several branches of the deep inferior epigastric vessels. The SIEA flap was inset beneath the contralateral breast through the midline. Results: Of 32 patients, 27 underwent DIEP flap breast reconstruction and simultaneous unaffected breast augmentation using 25 SIEA or 2 superficial circumflex iliac artery perforator (SCIP) flaps. All DIEP flaps survived, and total necrosis occurred in one SIEA flap. The mean weight of the final inset for DIEP flap reconstruction and SIEA or SCIP flap augmentation was 416 g and 112 g, respectively. Conclusions: Unilateral DIEP flap breast reconstruction and contralateral SIEA flap breast augmentation may be safely performed with satisfactory results.